THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN ENHANCING ENGLISH LANGUAGE SKILLS: A SYSTEMATIC REVIEW - Amalia Fatihah (PT Wahana Global Education, 2025)
The rapid advancement of artificial intelligence (AI) has greatly impacted English language education. Technologies such as natural language processing (NLP), chatbots, and intelligent tutoring systems offer flexible and adaptive learning environments that support the development of students’ speaking, writing, reading, and listening skills. Despite these benefits, further research is needed to evaluate the challenges and effectiveness of AI integration in language learning.This study presents a systematic review of how AI enhances English proficiency. Research published between 2020 and 2025 was analyzed using scholarly databases like Mendeley, ScienceDirect, and Taylor & Francis Online, following PRISMA guidelines. From an initial 11,768 articles, 476 were selected, and 23 were used as primary research data. The findings show that AI-powered tools improve language skills by offering personalized learning experiences and increasing student engagement. Tools such as AI chatbots and virtual tutors help improve spoken communication, while automated feedback systems enhance writing accuracy. However, challenges remain, including technological limitations, accessibility issues, and ethical concerns related to data privacy. Overall, AI has the potential to transform English education through personalized, practical, and interactive learning. Future research should focus on addressing current limitations and optimizing AI’s role in language instruction for learners worldwide.